Parents’ Knowledge, Attitude, and Misconceptions Towards Vaccination Practices for Their Children, as Determined by a Cross-Sectional Study in the City of Nalut, Libya (American Journal of Medical Science and Innovation, 2025)
The study aimed to determine the knowledge, attitude, and misconceptions of parents about the practice of childhood vaccinations. The study followed a descriptive, analytical approach in a cross-sectional study of workers in several schools (middle and high school), in addition to those attending the Sidi Khalifa Health Vaccination Center in the city of Nalut. The sample totaled 1,024 participants, and 24 participants were excluded. The questionnaire was distributed to the participants in addition to a face-to-face dialogue with the participants. The questionnaire consists of four axes: The first axis talks about the demographic characteristics of the participants, then three axes in order about the wrong beliefs, attitudes, and knowledge of parents about practicing vaccinations for their children. From December 2022 to July 2023, the study was conducted and the results were analyzed using SPSS. The results showed that the average age of the sample was 25-30 years. The educational level of the participants was 609 (60.9%) for those with university degrees. Marital status was divided between married (719), divorced (169), and widows (112). There was a correlation between the age of the participants and misconceptions about vaccinations (P-value< 0.05). It was also found that the level of misconceptions was low among the participants. The attitude of the participants towards the practice of vaccinations was positive 56.80%. It was also found that there was a correlation (P-value< 0.05) between the attitude towards practicing vaccinations and the educational level of the participants (36.78%) and their knowledge of vaccinations. An association was also found between the marital status of the participants and their tendency to practice vaccinations (X² = 163.815, P = 0.000).